Sosialisasi Booklet Persiapan Reproduksi Sehat Berkeluarga - Dina Dewi Anggraini; Yanik Muyassaroh; Aulia Fatmayanti (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Indonesian teenagers have relatively low knowledge about reproductive health (index value 52.4). On the one hand, sexual education plays an important role in forming positive attitudes so that teenagers can prepare for family life. Preparation for a family is a teenager's planning in determining the age of starting a family, determining the spacing of children's pregnancies, and participation in the Family Planning (KB) program. The aim of this community service activity is to socialize the booklet on preparing for healthy reproduction for a family to students of the Blora Midwifery Study Program, Diploma Three Program, Poltekkes Kemenkes Semarang in 2024. The method of this community service activity is by socializing lectures using booklet media. The target of the activity is 61 final year students who will soon graduate and face the world outside of education which can be applied by working, continuing their education, or even getting married.  So this community service activity needs to be carried out to equip students to better prepare for a healthy family life.